ANALISIS WACANA KRITIS MODERASI BERAGAMA DALAM PROGRAM LOG-IN EPISODE 30 SEASON 2 SEBAGAI MEDIA PEMBELAJARAN PAI ERA DIGITAL - luqmi, Fitra; Syaiful Anwar; Heny Wulandari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the critical discourse analysis of religious moderation values ​​in the YouTube program "Log In" Episode 30 Season 2 as a representation of digital media for Islamic Religious Education (PAI) learning in the Society 5.0 era, with a study focus on SMAN 9 Bandar Lampung. The "Log In" program, presented by Husein Ja'far Al-Hadar and Onadio Leonardo, is one of the moderate da'wah programs on YouTube that presents messages of tolerance, togetherness, and anti-extremism. The purpose of this study is to analyze the discourse of religious moderation values ​​in the program, identify representations of moderate Islamic education with materials sourced from digital platforms, and see its relevance to the context of PAI learning at SMAN 9 Bandar Lampung. This study uses a descriptive qualitative approach with the Critical Discourse Analysis method (Critical Discourse Analysis) model of Norman Fairclough, which includes three stages: text analysis, discourse practice (discursive), and social practice. Data were obtained through documentation of the YouTube broadcast "Log-In" Episode 30 Season 2, as well as observations and interviews with teachers and students at SMAN 9 Bandar Lampung. The results of the study indicate that the values ​​of religious moderation represented in the broadcast include tolerance, anti-violence, social justice, national commitment, critical thinking, and rahmatan lil 'alamin. These values ​​are classified into four main aspects of Islamic Religious Education (PAI) material: the Qur'an and Hadith, Creed, Morals, Jurisprudence, and Islamic History, and are directly relevant to strengthening Islamic Religious Education (PAI) learning indicators at the high school level.